m = (2 + 5) / (- 6 - 8)
m = 7 / (- 14)
m = (- 1/2)
y - 2 = (-1/2) (x + 6)
y = (-1/2)x - 3 + 2
y = (-1/2)x - 1
Or
2y = - x - 2
x + 2y + 2 = 0
2007-11-23 09:37:35
·
answer #1
·
answered by Como 7
·
2⤊
1⤋
^ but that wouldn't be in standard form. You can, however, use the y=mx+b formula to figure out your standard form equation.
m=(2- -5)/(-6-8)=7/-14=-1/2
2=-1/2(-6)+b
2=3+b
1=b
y=-(1/2)x+1
Now the slope in a standard form equation is the opposite coefficient of x over the coefficient of y, so that side of the equation would look like this:
2y+x
And the y-intercept is the other side of the equation divided by the coefficient of y. Since the coefficient of y is 2, and we know the y-intercept is 1, your standard form equation should look like this:
2y+x=2
y=mx+b is slope-intercept form, ax+by=c is standard form.
2007-11-23 17:30:52
·
answer #2
·
answered by topher098321 2
·
1⤊
2⤋
It's easiest to calculate the slope first, then use the point-slope equation.
To find slope, take
y2 - y1 / x2-x1
So,
2+5 / -6-8
= 7/-14
or
m=-1/2
Then, use the equation
y-y1 = m(x-x1)
So,
y+5=-1/2(x-8)
And, solve or isolate y by distributing the slope, m [-1/2]
y+5=-1/2x+4
Subtract 5 from both sides.
y=-1/2x-1
Standard form is Ax + By = C
So,
1/2x + y = -1
2007-11-23 17:33:30
·
answer #3
·
answered by crebeke 1
·
1⤊
1⤋
Step 1 (find the slope)
(x1,y1) = (8,-5)
(x2,y2) = (-6,2)
m = (y2 - y1)/(x2 -x1)
= (2 -(-5))/(-6 - 8)
= 7/-14
= -1/2
Step 2 (find equation) with (x1,y1) = (8,-5)
m = -1/2 (y - y1)/(x - x1)
-1/2 = (y -(-5))/(x - 8)
-1/2 = ( y + 5)/(x - 8)
-x + 8 = 2y + 10
-2y -x -2 = 0 (multiplied both sides by (-1))
2y +x +2 = 0
x + 2y + 2 = 0 (standard form Ax + By + C = 0)
2007-11-23 17:53:34
·
answer #4
·
answered by frank 7
·
0⤊
2⤋
Find the slope first. -5-2 over 8--6
-7/14
y=-1/2 x +b
2= -1/2 *-6 +b
2= 3 +b
-1 = b
y= -1/2 x -1
2007-11-23 17:30:48
·
answer #5
·
answered by mom 7
·
1⤊
2⤋
the formula for the line is
y=mx+b
so take a piece of graph paper and plot those 2 points.
the point where it crosses the y-axis is the "b" in the formula. Then use rise/run to give you the slope (which is "m" in the formula) if you do that step by step you should be able to get the correct answer
2007-11-23 17:24:30
·
answer #6
·
answered by Viv 3
·
1⤊
1⤋
(x1,y1)=(8,-5)
(x2,y2)=(-6,2)
formula:
y = mx + c
m,gradient/slope = (y2-y1)/(x2-x1) = (2--5)/(-6-8)=7/-14 = -0.5 or -1/2
to solve c put one of the co-ordinates into the above formula:
-5 = -0.5*8 + c
-5 = -4 + C
C = -1
Therefore the equation is:
y = -0.5x -1
2007-11-23 17:29:49
·
answer #7
·
answered by Istiaque Choudhury, BEng (Hons) 4
·
1⤊
2⤋